Gain improvement of microstrip patch antenna using CLS split ring resonator metamaterial - Katiyar, P.R.; Mahadi, W.N.L.B.W. (2015)
Metamaterials are artificial materials with negative permittivity and permeability. Metamaterials due to their unique negative parameter are capable of focusing the electromagnetic energy incident upon them. This focusing of electromagnetic energy is used to increase the gain of microstrip patch antenna. A capacitive loaded strip (CLS)-loaded split ring resonator is used to form a multilayer array of metamaterial and used in front of microstrip patch antenna to enhance far-field gain of antenna. An accurate simulation model is created and analyzed using CST. The simulated model is then fabricated and measured in fully anechoic chamber for validation. The far-field gain of regular patch antenna with and without metamaterial is measured in anechoic chamber. The increase in gain by 4 dB is measured at 95 mm from antenna. The beam focusing property is also evident from 3 dB beamwidth of antenna which is reduced to 42.01 degrees.